2017
DOI: 10.1038/s41598-017-01036-4
|View full text |Cite
|
Sign up to set email alerts
|

Refractive index tomograms and dynamic membrane fluctuations of red blood cells from patients with diabetes mellitus

Abstract: In this paper, we present the optical characterisations of diabetic red blood cells (RBCs) in a non-invasive manner employing three-dimensional (3-D) quantitative phase imaging. By measuring 3-D refractive index tomograms and 2-D time-series phase images, the morphological (volume, surface area and sphericity), biochemical (haemoglobin concentration and content) and mechanical (membrane fluctuation) parameters were quantitatively retrieved at the individual cell level. With simultaneous measurements of individ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(43 citation statements)
references
References 63 publications
5
38
0
Order By: Relevance
“…As shown in the AFM images in Figure 9 a (left), a deeper dimple region is present in healthy RBCs, while a shallow dimple or no dimple occurs in diabetic RBCs. Similar results were presented by Lee et al [ 151 ] via common-path diffraction optical tomography (cDOT). The 2D membrane height maps of RBCs from healthy controls and from diabetic patients in Figure 9 a (right) imply a loss of the center dimple region for their representative diabetic RBCs.…”
Section: Diabetes Mellitussupporting
confidence: 87%
See 2 more Smart Citations
“…As shown in the AFM images in Figure 9 a (left), a deeper dimple region is present in healthy RBCs, while a shallow dimple or no dimple occurs in diabetic RBCs. Similar results were presented by Lee et al [ 151 ] via common-path diffraction optical tomography (cDOT). The 2D membrane height maps of RBCs from healthy controls and from diabetic patients in Figure 9 a (right) imply a loss of the center dimple region for their representative diabetic RBCs.…”
Section: Diabetes Mellitussupporting
confidence: 87%
“…The stretched states of N-RBC and D-RBC2 under an external tensile force of 100 pN are also presented in Figure 9 c. It is obvious to see the reduced cell stretching response of D-RBC2 against N-RBC at the same tensile force. Chang et al [ 152 ] also found a diminished membrane fluctuation reflected in the narrower fluctuation distribution in Figure 9 d of the T2DM RBCs compared to the normal RBCs, which is qualitatively consistent with experimental work ( Figure 9 c) by Lee et al [ 151 ]. As for T2DM RBCs with the abnormal near-oblate shape (D-RBC2 and D-RBC3), much narrower fluctuation distributions are presented (see Figure 9 c).…”
Section: Diabetes Mellitussupporting
confidence: 87%
See 1 more Smart Citation
“…Second, the flicking of the RBC membrane at the time scale of 2 s is related to biophysical properties of the membrane 37 and has been quantified with QPI to range from 49 to 60 nm. 16 Considering the thickness of healthy RBCs being about 2 μm, the flicking causes less than 3% fluctuations in the volume. Therefore, it was ignored in this study.…”
Section: Evaluation Of the Accuracy Of The 3d-arg Methodsmentioning
confidence: 99%
“…10 The physical thickness and three-dimensional (3-D) RI maps of RBCs can be reconstructed from multiple 2-D phase images acquired at various illumination directions using diffraction tomography techniques. 14 Recently, studies have characterized 3-D morphological indices of RBCs including the surface area, volume, and sphericity and have demonstrated significant differences between RBCs from the cord blood of newborn infants and that of maternal or nonpregnant women 15 and between normal RBCs and RBCs from patients with diabetes mellitus, 16 malaria, 14 iron-deficiency anemia, 17 reticulocytes, 17 hereditary spherocytosis, 17 and sickle-cell disease. 11,[17][18][19] These 3-D RBC parameters provide additional morphometrics for hematologists to better distinguish and understand blood diseases related to deformation of RBCs.…”
Section: Introductionmentioning
confidence: 99%